Improvement of carrier distribution in dual wavelength light-emitting diodes - 司朝 魏同波 张宁 马骏 王军喜 李晋闽 (Journal of semiconductors, 2013)
The effect of different barriers between green and blue light regions in dual wavelength light emitting diodes was studied. Compared with a traditional sample, electroluminescence and photoluminescence spectra of the newly designed samples showed peak intensity improvements and smaller blue-shifts with increasing injection current level, and the bottom quantum-wells light emitting is enhanced. All these phenomena can be ascribed to reduced barrier thickness and indium doping in the quantum-barrier influencing electric fields and more holes injecting into the bottom QWs.